MANFAAT YOGA DAN MEDITASI TRADISIONAL TERHADAP EFIKASI DIRI: NARRATIVE REVIEW - Agung Setiabudi; I Gede Eka Agung Agastya Punia; Putu Setiani; Lussy Ayu Puspita; Kadek Satya Manggala (Pascasarjana Universitas Hindu Indonesia, 2026)
Self-efficacy refers to an individual's belief in their ability to organize and execute the actions necessary to achieve established goals. This concept significantly influences mental health, academic performance, and quality of life. Traditional yoga and meditation have been widely studied as effective complementary mind-body approaches to improving psychological well-being. This narrative review aims to synthesize recent scientific findings regarding the benefits of yoga practices and traditional blends on self-efficacy. A literature search was conducted through primary scientific data using keywords related to yoga, meditation, mindfulness, and self-efficacy. The review results indicate that yoga and meditation practices consistently contribute to increased self-efficacy, mediated through improved emotional regulation, mindfulness, perceived self-control, and mastery experiences. These findings confirm the potential of traditional yoga and meditation as relevant non-pharmacological interventions to support the strengthening of individual psychological capacities.